(untitled) (Journal of the Bangladesh Agricultural University, 2011)
An economic anylysis was made to determine the cost of fish production in the floodplains at Daudkandi Upazilla in Comilla district during the period form January to April, 2007. Survey method was followed to collect data from 20 floodplain aquaculture projects. The projects record books and personal interviews of the NGOs and Fisheries officers were the main instruments of data collection. Statistical tools such as: range, mean, standard deviation and percentage were employed for analysis of data. The Cobb-Douglas production function model was used to estimate the values of co-efficients and related statistics of production function of fish culture in floodplains. Out of eleven explanatory variables, seven co-efficients had positive sign while only four co-efficients showed negative sign. The co-efficients bearing positive sign i.e., embankment construction, nursery and land lease, fertilizer and lime, fingerlings, feed, labor and staff wages and miscellaneous cost made positive impact on the farm income, while the co-efficients having negative sign i.e., area of floodplain, Office management, compensation and harvesting and marketing cost decreased the farm income. Summation of the production co-efficients i.e., return to scale (Σbi) was found 1.023 which implies that per one taka investment in floodplain fish culture will give rise to a profit of Tk. 1.02. The value of R2 was found 0.892, which means that the variations in farm income could be explained to the extent of 89.2% by the included variables. The remaining 10.8% variations could not be accounted for by the multiple regression analysis. Average fish production in the selected floodplains was 2920.43 kg/ha of which production of cultured fish and indigenous fish was 2697.35 and 223.08 kg/ha respectively. The cost of fish production, total return and net income were estimated Tk. 1,153,08.55, 1,76,385.49 and 61,076.94 /ha. respectively. Benefit cost ratio was found 1.53. Keywords: Floodplain; Aquaculture; Economic analysis; Resource productivity; Community DOI: 10.3329/jbau.v8i2.7945 J. Bangladesh Agril. Univ. 8(2): 323-332, 2010